Tačnost izračunavanja osmolarnosti seruma kod male dece - Berska, Joanna; Bugajska, jolanta; Sztefko, Krystyna (Journal of Medical Biochemistry, 2022)
Background. Serum osmolality can be measured (Omeas) or calculated (Ocal). Many formulas for Ocal have been already published, but data regarding the most accurate equation in small babies is not available. Thus, we aim to compare Omeas and Ocal obtained by different formulas in newborns and small children. Methods. The study included 280 serum samples taken from children, from the first day of life to 2 years (mean age 8.2 ± 7.6 months) treated in the University Children’s Hospital in Krakow. The serum osmolality was measured by osmometer and calculated by 8 common formulas. Results. The mean value of Omeas (285.8±5.1 mOsm/kgH2O) was significantly different as compared to the mean values of Ocal (p<0.01) for all formulas, except Ocal obtained by the formula: 1.86*(Na+K)+1.15*Glu+Urea+14. According to Bland-Altman analysis, this formula showed the best performance for estimating osmolality. In children under 3 months of life Passing-Bablok regression indicated both systematic and proportional error for results obtained by each formula compared to the measured values. Conclusions. To calculate osmolarity in children aged between 3 months and 2 years old the following equations: 1.86*(Na+K)+1.15*Glu+Urea+14 might be used, whereas serum osmolality in children up to 3 month of life should be measured.